Appropriate farm machinery - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
The 57th International Agricultural Machinery Show (SIMA) held in Paris from 9th to 16th March 1986 included a collective stand for small-scale manufacturers who are not usually represented at the show. At this stand visitors were given a good...